Educación en derechos humanos en la educación superior: una abordaje - Marcia Maria Fernandes de Oliveira; Hecilda Aparecida Carneiro Santos; Michelle Nalepa (Universidade Federal de Rondônia, 2020)
This essay presents an approach on Human Rights Education focused on the current higher education. To this goal, it was used the survey of bibliographical references that discuss this subject, from the purpose of knowing the state of knowledge, based on the assumptions (ROMANOWSKI; ENS, 2006). The Contributions From Authors Such As Monteiro, Aída Maria; Candau, Vera Maria; Ferreira, Lucia De Fátima Guerra; Zenaide, Maria De Nazaré; Dias, Adelaide Alves; Tavares, Celma; Rodino, Ana Maria; Sacavino, Suzana; Santos, Bonaventure de Souza; among others, were fundamental for understanding the findings of research on human rights education in higher education.